2011
DOI: 10.1016/j.nucmedbio.2010.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Labeling, stability and biodistribution studies of 99mTc-cyclized Tyr3-octreotate derivatives

Abstract: Introduction-To probe the interplay between radiotracer stability and somatostatin receptor affinity, Tyr 3 -octreotate and six variations of its peptide sequence, for which the Re-cyclized products were previously reported, were radiolabeled with 99m Tc and investigated for their in vitro stability.Methods-Radiolabeling of the peptides was effected by ligand exchange from 99m Tcglucoheptonate, and the desired products were purified by radio-RP-HPLC. The in vitro stability in phosphate-buffered saline, mouse s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
(27 reference statements)
1
16
0
Order By: Relevance
“…This occurrence has been previously reported by Radford et al . for another class of [ 99m Tc]Tc‐DPA labeled peptides for whose the addition of a radioprotective agent such as gentisic acid and an adjustment of the pH to 7.4 was necessary to improve their stability . High challenge stability confirmed that the coordination between [ 99m Tc]Tc‐tricarbonyl and DPA apparently is sufficient for in vivo use as it has been described earlier …”
Section: Resultssupporting
confidence: 81%
“…This occurrence has been previously reported by Radford et al . for another class of [ 99m Tc]Tc‐DPA labeled peptides for whose the addition of a radioprotective agent such as gentisic acid and an adjustment of the pH to 7.4 was necessary to improve their stability . High challenge stability confirmed that the coordination between [ 99m Tc]Tc‐tricarbonyl and DPA apparently is sufficient for in vivo use as it has been described earlier …”
Section: Resultssupporting
confidence: 81%
“…Though 99m Tc has relatively low decay energetics, we have observed radiolysis in other peptide-based complexes labeled with 99m Tc. [18] The described stability procedure was modified by the addition of GA to the incubation vial and pH readjustment to 7.4 using a 1 M NaHCO3 solution. The histidine/GA results demonstrated a marked improvement in stability, with 99m TcL-sst2-ANT remaining highly intact (≥99%) through 24 hours, supporting the radiolysis hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…In another effort, modifications in the peptide sequence of the somatostatin‐receptor‐targeted octreotate led to the preparation of cyclized 99m Tc analogues. In these radioconjugates, the disulfide bridge between two distant cysteine residues of the peptide was prereduced and the thiol groups generated were made available for oxotechnetium cyclized complexes …”
Section: Technetium‐99m Labeling Strategies For the Development Of Tamentioning
confidence: 99%
“…In these radioconjugates, the disulfide bridge between two distant cysteine residues of the peptide was prereduced and the thiol groups generated were made available for oxotechnetium cyclized complexes. 124 Finally, the "integrated" approach, where the metal-chelate part forms the pharmacophore moiety, can be applied ( Figure 10). In this approach, careful design of the chelator must be applied to mimic the structure of the bioactive molecule after complexation of the radiometal.…”
Section: Technetium-99m Labeling Of Small Molecules or Peptidesmentioning
confidence: 99%